PENERAPAN FUNGSI MANAJEMEN TERHADAP PENINGKATAN PRESTASI KERJA PEGAWAI DI KANTOR KECAMATAN MAIWA KABUPATEN ENREKANG - Aris Munandar (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2017)
This study aims to (a) determine the application of management functions to improve employee performance at the Maiwa District Office, Enrekang Regency. (b) Knowing what factors influence the application of management functions to improving employee performance at the Maiwa sub-district office, Enrekang Regency. The number of population and samples in this study were the same, namely 36 people. The sampling technique used is saturated sampling (census). Data collection techniques used are (1) observation, (2) interviews, (3) questionnaires, and (4) literature research. The collected data was then analyzed using frequency and percentage tables. The results showed that the application of management functions to improve employee performance at the Maiwa District office, Enrekang Regency was in the good category with percentage achievement (69.73%). The factors that influence the management function to improve employee performance at the Maiwa District office, Enrekang Regency are: motivation (93 %), self-regulation (86 %), goal achievement (80.5 %), work quality (84 %), quantity work (77 %), and work initiative (86 %).